Penggunaan E-learning 2 UNP Dalam Pembelajaran di Masa Pademi Covid-19 - Rizki Muhammad Ramadhan; Ofianto Ofianto (Jurusan Sejarah FIS UNP, 2021)
Abstract This research was motivated by the occurrence of the COVID-19 pandemic that hit Indonesia, especially the State University of Padang, which caused the change of face-to-face learning systems to fully online learning systems using E-Learning 2 UNP. The purpose of this study was to see the level of use and constraints in the use of E-Learning 2 UNP by lecturers and students of the UNP Department of History. This type of research is descriptive-evaluative research using the Mix Methods method (quantitative and qualitative). Quantitative research was conducted first by distributing questionnaires to 11 History lecturers and 82 History students, after processing the results of the questionnaire were obtained followed by conducting interviews with History lecturers and students to obtain qualitative research results. Simple random sampling technique was chosen as a sampling technique by considering the age level of the respondent and the level of homogeneity of the respondent. After the research data were obtained and the results were obtained that the level of use of E-Learning 2 UNP by lecturers and students majoring in history was VERY GOOD with a percentage of 91%, but in the use of E-Learning 2 UNP features there were several features that were rarely used, namely the IMS Content Package feature. , BigBlueButtonBN, Quiz, SCORM, Via, Workshop, Survey, Glossary, Wiki, Database, External Tool. The cause of the rarely used of these features is constrained by the lack of learning time, the similarity of use in several features, adjusting to the material being taught, the limited ability of the lecturer to use these features. And some of the features that are often used are File, Folder, URL / Link, Label, Page, Book, Attendance, Lesson, Chat, Choice, Forum, Feedback, Assignment. The reason for the frequent use of these features is the ease with which these features are used, according to the needs of the learning material. Then found the obstacles felt by lecturers and students, namely constrained by an unstable network, E-Learning 2 UNP which often errors at certain hours, wasteful quotas, constrained by technology and its use. Keywords: Historical Online Learning, E-Learning 2 UNP. Abstract Penelitian ini dilatarbelakangi oleh terjadinya pandemic COVID-19 yang melanda Indonesia khususnya Universitas Negeri Padang yang menyebabkan bergantinya sistem belajar tatap muka menjadi sistem belajar daring sepenuhnya yang menggunkan E-Learning 2 UNP. Tujuan penelitian ini adalah untuk melihat tingkat penggunaan dan kendala dalam penggunaan E-Learning 2 UNP oleh dosen dan Mahasiswa Jurusan Sejarah UNP. Jenis penelitian ini adalah, penelitian Deskriptif-Evaluatif dengan menggunakan metode Mix Methods (kuantitatif dan kualitatif). Penelitian kuantitatif dilakukan terlebih dahulu dengan menyebar angket kepada 11 dosen Sejarah dan 82 mahasiswa Sejarah, setelah mengolah hasil angket didapatkan dilanjutkan dengan melakukan wawancara kepada dosen dan mahasiswa Sejarah untuk mendapatkan hasil penelitian kualitatif. Teknik simple random sampling dipilih sebagai teknik pengambilan sampel dengan mempertimbangkan tingkatan umur dari responden dan tingkat homogenitas dari responden. Setelah data penelitan dioleh dan didapatkan hasil bahwa tingkat penggunaannya E-Learning 2 UNP oleh dosen dan mahasiswa jurusan sejarah SANGAT BAIK dengan persentase 91% akan tetapi dalam penggunaan fitur-fitur E-Learning 2 UNP terdapat beberapa fitur yang jarang digunakan yaitu fitur IMS Content Package, BigBlueButtonBN, Quiz, SCORM, Via, Workshop, Survey, Glossary, Wiki, Database, External Tool. Penyebab jarangnya digunakan fitur-fitur tersebut adalah terkendala keterbatasan waktu pembelajaran yang kurang, adanya kesamaan kegunaan dibeberapa fitur, menyesuaikan dengan materi yang diajar keterbatasan kemampuan dosen dalam menggunakan fitur-fitur tersebut. Dan beberapa fitur yang sering digunakan yaitu fitur File, Folder, URL/Link, Label, Page, Book, Attendance, Lesson, Chat, Choice, Forum, Feedback, Assigment. Penyebab seringnya digunakan fitur-fitur tersebut adalah mudahnya fitur-fitur tersebut digunakan, sesuai dengan kebutuhan materi pembelajaran . Lalu ditemukan kendala yang dirasakan oleh dosen dan mahasiswa yaitu terkendala jaringan yang tidak stabil, E-Learning 2 UNP yang sering eror di jam tertentu, kuota yang boros, terkendala teknologi dan penggunaannya. Kata Kunci: Pembelajaran Daring Sejarah, E-Learning 2 UNP.